Failure Analysis of Galvanized Iron Pipe at Perumda Tirta Kanjuruhan - Pramita, Cynthia Rosa; Suprapto, Agus; Widyastuti, Ike (TRANSMISI, 2023)
The most commonly used type of water pipe is iron pipe or commonly called Galvanized Iron pipe. The disadvantage of GI pipe is that it rusts easily. So it can result in degradation, decreased efficiency and construction, poor water quality, and higher maintenance costs. Water channeled through rusty pipes will pollute the water and adversely affect the health of those who consume it. This study aims to determine the factors causing failures of GI pipe in the distribution pipeline that have failed due to corrosion. The tested pipes is 1/2"ᴓ sized, 5-year-old corroded pipe whose distribution uses a gravity system and a pumping system. To support this analysis, operational data on fluid and environmental conditions around the pipeline are needed, observations on macro and micro structures, and hardness testing. The corrosion rate is calculated through the thickness loss method and the corrosion rate in the gravity system is 0.153 mm / year that higher than pipe in pumping system. Microstructure observations support the characterization of the material that this pipe is a mild steel, where this type of steel has a high Fe content so it is vulnerable to corrosion attacks. Rockwell hardness testing showed that the corrosion rate is directly proportional to the hardness value of the pipeline. The results of the analysis show that the environment around the pipe which has low soil resistivity and high humidity levels is the main factor in the occurrence of uniform corrosion of the pipe. The selection of inappropriate materials is also supportive as the cause of corrosion occurring.